KEPASTIAN HUKUM MENGENAI PERBEDAAN ANTARA PUTUSAN MAHKAMAH AGUNG DAN PUTUSAN MAHKAMAH KONSTITUSI TERKAIT PENCALONAN PERSEORANGAN PESERTA PEMILU ANGGOTA DPD - Rasji .; Cinthia . (Faculty of Law - Tarumanagara University, 2019)
Indonesia is a country based on the law (rechstaat) whose basis is stated in Article 1 Paragraph (3) of the UUD NRI 1945. The essential principles of the rule of law based on Article 24 Paragraph (1) of the UUD NRI 1945 are the guarantee of the organizer of the power of an independent judicial institution without interference from other parties to hold a court to uphold law and justice. Ideally, the results of the two institutions' decisions do not cause problems in society. However, the results of the decisions of the two institutions are still found differently regarding the issue of nominating individual participants in the members of the Regional Representatives Council. Any other way, the results of the Constitutional Court ruling prohibited members of the Regional Representatives Council who were still in the position of administrators of political parties. Meanwhile, the decision of the Supreme Court allows candidates for members of the Regional Representatives Council who are still in the position of managing political parties. In this study, the researcher will examine the differences between the Supreme Court's decision and the Constitutional Court's decision regarding the nomination of individual participants in the Regional Representatives Council by using normative legal methods and conducting interviews as supporting data. The results of the study revealed that based on the legal basis and authority of the institution, the verdict that had legal certainty regarding the nomination of individual participants in the Regional Representatives Council election was the decision of the Constitutional Court.